Solvent Extraction and Spectrophotometric Determination of Cu(II) with 3,4-Diaminobenzophenone - SHANBHAG, BHOOSHAN; GOSALIA, RIDDHI (Asian Journal of Chemistry, 2010)
A method is proposed for the solvent extraction and spectrophotometric determination of Cu(II) at microgram levels using 3,4-diaminobenzophenone as a complexing agent. Cu(II) forms a wine red coloured complex with 3,4-diaminobenzophenone, which can be extracted into chloroform under optimum conditions. The chloroform extract shows maximum absorbance at 400 nm wavelength. Beer’s law was obeyed over the range of 50 to 100 μg of Cu(II). The stoichiometry of the extracted species was found to be 1:2. The interference due to diverse cations and anions has been studied.